Description of the pupa, female and male genitalia of Aedes (Howardina) guerrero Berlin and first record of Ae. (How.) guatemala Berlin (Diptera: Culicidae) in Puebla, Mexico - Rivera-García, Karina D.; Mendez-Andrade, Alejandro; Díaz-Osorio, Alicia C.; Ibáñez-Bernal, Sergio; Sandoval-Ruiz, César Antonio (Zootaxa, 2023)
The pupa, female and male genitalia of Aedes (Howardina) guerrero Berlin, 1969 are described and illustrated for the first time. Additionally, the geographical distribution of Ae. (How.) guatemala Berlin, 1969 is extended. Valuable information on the distribution, larval habitats, taxonomy and keys to species within the Sexlineatus Section of the subgenus Howardina is provided.